2019
DOI: 10.1016/j.bja.2019.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Management of suspected immediate perioperative allergic reactions: an international overview and consensus recommendations

Abstract: Suspected perioperative allergic reactions are rare but can be life-threatening. The diagnosis is difficult to make in the perioperative setting, but prompt recognition and correct treatment is necessary to ensure a good outcome. A group of 26 international experts in perioperative allergy (anaesthesiologists, allergists, and immunologists) contributed to a modified Delphi consensus process, which covered areas such as differential diagnosis, management during and after anaphylaxis, allergy investigations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
224
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(242 citation statements)
references
References 108 publications
(172 reference statements)
2
224
0
16
Order By: Relevance
“…We also suspected anaphylaxis caused by propofol or rocuronium, as hypotension did not respond to conventional drugs such as ephedrine and phenylephrine. Hypotension, bronchospasm, angioedema, and dermatological symptoms are common clinical signs of perioperative allergic reactions [11]. In our case, hypotension was the only symptom.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We also suspected anaphylaxis caused by propofol or rocuronium, as hypotension did not respond to conventional drugs such as ephedrine and phenylephrine. Hypotension, bronchospasm, angioedema, and dermatological symptoms are common clinical signs of perioperative allergic reactions [11]. In our case, hypotension was the only symptom.…”
Section: Discussionsupporting
confidence: 48%
“…A recent review reported that it is important to consider anaphylaxis as a differential diagnosis when perioperative hypotension or bronchospasm do not respond to conventional therapy during general anesthesia [11]. We also suspected anaphylaxis caused by propofol or rocuronium, as hypotension did not respond to conventional drugs such as ephedrine and phenylephrine.…”
Section: Discussionmentioning
confidence: 94%
“…In our case, we found a marked increase in serum tryptase at 1 h after the reaction (174 μg/L) compared to the baseline level (2.1 μg/L). Since an increase in serum tryptase at the time of a suspected reaction to above 1.2 × baseline + 2 μg/L is considered clinically relevant [15], the results suggested the occurrence of a strong hypersensitivity reaction. Significant elevation of plasma histamine levels at 1 h after the reaction (271.7 nmol/L) compared to baseline levels (6.3 nmol/mL) also supported our diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…National Audit Project (NAP6), 2 and in recent publications from European and international working groups making recommendations on the management and investigation of perioperative hypersensitivity reactions. 1,3 In the following, two algorithms are presented based on recent hypersensitivity. In some cases, an allergic mechanism is not obvious and tryptase may not be elevated, or not taken.…”
Section: Such Collaborations Have Been Endorsed In the Recent 6th Brimentioning
confidence: 99%
“…Once it has been decided that an allergic mechanism is likely or cannot be ruled out, a The presented algorithms are a truncated version of recommendations made in the 2019 EAACI position paper 1 and other recent international publications. [2][3][4][5][6][7] Work in this field was initiated in France 8 and Australia, 6 and is now expanding rapidly with increasing international collaborations. This publication provides an overview only, and more detailed information can be found in the referenced guidelines and articles.…”
Section: Such Collaborations Have Been Endorsed In the Recent 6th Brimentioning
confidence: 99%